Integrative Production Technology for High-Wage Countries - Brecher, Christian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Industrial production in high-wage countries like Germany is still at risk. Yet, there are many counter-examples in which producing companies dominate their competitors by not only compensating for their specific disadvantages in terms of factor costs (e.g. wages, energy, duties and taxes) but rather by minimising waste using synchronising integrativity as well as by obtaining superior adaptivity on alternating conditions. In order to respond to the issue of economic sustainability of industrial production in high-wage countries, the leading production engineering and material research scientists of RWTH Aachen University together with renowned companies have established the Cluster of Excellence (3z(BIntegrative Production Technology for High-Wage Countries(3y(B. This compendium comprises the cluster$1 (Bs scientific results as well as a selection of business and technology cases, in which these results have been successfully implemented into industrial practice in close cooperation with more than 30 companies of the industrial production sector.s
Introduction -- Integrative Production Technology for High-Wage Countries -- Individualised production -- Virtual production systems -- Hybrid production systems -- Self-optimising production systems -- Integrative Business- und Technology Cases -- Subject index.
Keywords: Engineering; Industrial engineering; Sustainable development; Engineering; Industrial and Production Engineering; Production/Logistics/Supply Chain Management; Sustainable Development